(x−y)3+(y−z)3+(z−x)3(x2−y2)3+(y2−z2)3+(z2−x2)3 is = ?(x−y)3+(y−z)3+(z−x)3(x2−y2)3+(y2−z2)3+(z2−x2)3 is = ?\frac{{{{\left( {x - y} \right)}^3} + {{\left( {y - z} \right)}^3} + {{\left( {z - x} \right)}^3}}}{{{{\left( {{x^2} - {y^2}} \right)}^3} + {{\left( {{y^2} - {z^2}} \right)}^3} + {{\left( {{z^2} - {x^2}} \right)}^3}}}{\text{ is = ?}}" /> (x−y)3+(y−z)3+(z−x)3(x2−y2)3+(y2−z2)3+(z2−x2)3 is = ?(x−y)3+(y−z)3+(z−x)3(x2−y2)3+(y2−z2)3+(z2−x2)3 is = ?\frac{{{{\left( {x - y} \right)}^3} + {{\left( {y - z} \right)}^3} + {{\left( {z - x} \right)}^3}}}{{{{\left( {{x^2} - {y^2}} \right)}^3} + {{\left( {{y^2} - {z^2}} \right)}^3} + {{\left( {{z^2} - {x^2}} \right)}^3}}}{\text{ is = ?}}" /> (x−y)3+(y−z)3+(z−x)3(x2−y2)3+(y2−z2)3+(z2−x2)3 is = ?(x−y)3+(y−z)3+(z−x)3(x2−y2)3+(y2−z2)3+(z2−x2)3 is = ?\frac{{{{\left( {x - y} \right)}^3} + {{\left( {y - z} \right)}^3} + {{\left( {z - x} \right)}^3}}}{{{{\left( {{x^2} - {y^2}} \right)}^3} + {{\left( {{y^2} - {z^2}} \right)}^3} + {{\left( {{z^2} - {x^2}} \right)}^3}}}{\text{ is = ?}}" />
Post your Comments